Genetic and Molecular Mechanisms Conferring Heat Stress Tolerance in Tomato Plants - Hoshikawa, Ken; Pham, Dung; Ezura, Hiroshi; Schafleitner, Roland; Nakashima, Kazuo (Frontiers in Plant Science, 2021)
Climate change is a major threat to global food security. Changes in climate can directly impact food systems by reducing production and genetic diversity of crops and their wild relatives, thereby restricting future options for breeding improved varieties, and reducing the ability to adapt crops to future challenges. The global surface temperature is predicted to rise by an average of 0.3 °C during the next decade, and the Paris Agreement (Paris Climate Accords) aims to limit global warming to below an average of 2 °C, preferably to 1.5 °C compared to pre-industrial levels. Even if the goal of the Paris Agreement can be met, the predicted rise in temperatures will increase the likelihood of extreme weather events, including heat waves, making heat stress a major global abiotic stress factor for many crops. Heat stress can have adverse effects on plant morphology, physiology, and biochemistry during all stages of vegetative and reproductive development. In fruiting vegetables, even moderate heat stress reduces fruit set and yields, and high temperatures may result in poor fruit quality. In this review, we emphasize the effects of abiotic stress, especially at high temperatures, on crop plants, such as tomatoes, touching upon key processes determining plant growth and yield. Specifically, we investigated the molecular mechanisms involved in heat stress tolerance and the challenges of developing heat-tolerant tomato varieties. Finally, we discuss a strategy for effectively improving the heat tolerance of vegetable crops.